Pelatihan Pembuatan Tote Bag Ramah Lingkungan dengan Penerapan Teknologi Ecoprint Teknik Pounding pada Ibu-ibu PKK RT 03 Dukuh Sanggrahan, Tirtoadi, Mlati, Sleman - Yuliana Rizka Handayani; Daereo Dzakwan Putra Widana; Rachael Arnesta Torey; Anya Yuniza D; Annisa Hafshah A; Unan Yusmaniar Oktiawati (Direktorat Pengabdian kepada Masyarakat, 2024)
Ecoprint is a technique to create patterns on fabric or other materials using natural substances as dyes. This ecoprint technique employs natural materials such as leaves and flowers. Nowadays, ecoprint can be applied to various items, including tote bags. The production of ecoprinted tote bags represents a new step in promoting environmentally friendly products. During the Student Community Service Learning (Kuliah Kerja Nyata or KKN) of the second period of academic year 2023 at Gadjah Mada University, in Unit YO057 located in the Mlati region, specifically in the Tirtoadi Village, the theme of